The effects of EU fisheries partnership agreements on fish stocks and fishermen: The case of Cape Verde - Matthias Mundt (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2012)
The viewpoints of 30 Cape Verdean fishermen are used together with an analysis of the state of tuna stocks in the Atlantic Ocean to question the EU's claim that their fleet only targets surplus species. Additionally, local marine catches of the artisanal and semi-industrial fleet are evaluated and the importance of the fisheries sector for the inhabitants of Cape Verde is shown. It is argued that even though the EU condemns illegal, unreported and unregulated fishing (IUU); their approach to stop IUU fails. In order to support this hypothesis, monitoring of the European fleet, movements of tuna fish and coverage of recent Fisheries Partnership Agreements (FPAs) are analysed. Finally, the prevalence of fisheries subsidies is discussed. Here, the focus is set on those subsidies embedded in two FPAs between the EU and Cape Verde. It is concluded that the subsidies provided by the EU to their fleet increase the problem of overfishing in Cape Verde. A theoretical solution is discussed and it is proposed that the external component of the European fisheries policy, namely Fisheries Partnership Agreements, has to change toward an association that deserves the name partnership.
Keywords: O1; Q5; Q57; Q58; 330; Cape Verde; artisanal fishing; overfishing; Fisheries Partnership Agreement; IUU; fisheries subsidies; Yellowin tuna; Bluefin tuna; Skipjack; European fishing policy